The Bologna process in the context of teacher education: a model analysis - Pereira, Cristina (2011)
Teachers and pre-school teachers’ education appears as a vital strategic issue to operate changes of different kinds in education and, consequently, on concepts about the profession and teachers’ professionalism. The present legislation concerning Professional Qualifications for Teaching (Law n.4372007) was created in the context of the Higher Education reorganization according to the Bologna Process. By situating the professional qualification of pre-school teachers and primary school teachers at the second cycle level (Master’s), this law may contribute to reinforce the recognition of these actors’ importance in the promotion of quality development, which is so necessary in the Portuguese society, and necessarily refers to the need of a demanding, qualitative initial teacher education. Another crucial aspect in this law relates to the possibility of extending teachers’ practice into two basic education cycles. Having this context as background, the present communication intends to present and analyse some of the foundations of the curriculum organization for the Master’s Cycle in Pre-School and Primary School Education from the Castelo Branco School of Education, giving special attention to the integration of educational research methodologies in supervised teaching practice. We conclude with the presentation and analysis of the results obtained in the experimental version of questionnaire “Concepções sobre Processos Investigativos e Prática Docente” (Concepts on Research Processes and Teaching Practice) to the master’ students.